2022
DOI: 10.1039/d1fo04102a
|View full text |Cite
|
Sign up to set email alerts
|

In vitro simulated semi-dynamic gastrointestinal digestion: evaluation of the effects of processing on whey proteins digestibility and allergenicity

Abstract: The effect of thermal processing on digestibility of milk proteins should be better understood as this can greatly affect their immunoreactivity. The aim of this study was to evaluate the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Gasparini et al. (2022) demonstrated that compared with natural peptides, heat‐treated β‐lactoglobulin peptides were more difficult to achieve transepithelial transport to sensitize. On the other hand, Ma et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gasparini et al. (2022) demonstrated that compared with natural peptides, heat‐treated β‐lactoglobulin peptides were more difficult to achieve transepithelial transport to sensitize. On the other hand, Ma et al.…”
Section: Discussionmentioning
confidence: 99%
“…It observed a decrease in the contents of αhelix and β-turn in the secondary structure, alterations in the tertiary structure, and reduced surface hydrophobicity following the four cooking methods, which might affect the transport of egg allergens in the gastrointestinal tract. Gasparini et al (2022) demonstrated that compared with natural peptides, heat-treated β-lactoglobulin peptides were more difficult to achieve transepithelial transport to sensitize. On the other hand, Ma et al (2013) reported that heating and glycation reduced the content of β-sheet while increasing the content of β-turn, leading to the disruption of several IgE epitopes of Gal d 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bos d 5 glycation drastically reduced its transcytosis probably due to partial unfolding, and/or aggregate formation (Perusko et al., 2018). Likewise, the native form of the allergenic peptide derived from β‐lactoglobulin, KIDALNENKVLVL, is more easily transported than their monolactosylated forms through the Caco‐2 monolayer (Gasparini et al., 2022). Additionally, it was suggested that protein transport is glycosylation specific since the transport rate of bovine serum albumin glycosylated with α‐Gal was different from an NA1 glycosylated form, a carbohydrate modification of similar size (Krstić Ristivojević et al., 2020).…”
Section: Features That Impact Allergen Transport (Mie1‐3)mentioning
confidence: 99%
“…Overall, eleven glycation sites and five glycation groups of parvalbumin through the Maillard reaction were identified by Nano-LC-MS/MS. Glycation resulted from the Maillard reaction may destroy the conserved structure and the predicated epitopes in parvalbumin, which can further affect the immunogenicity and allergenicity of the parvalbumin [43]. The amino acid coded in red was corresponded to the epitope of Baltic cod allergen M Gad c1.…”
Section: Identification Of Glycation Sites In Parvalbuminmentioning
confidence: 99%